2017
DOI: 10.1186/s12864-016-3397-4
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of seed composition traits in wild soybean (Glycine soja)

Abstract: BackgroundCultivated soybean (Glycine max) is a major agricultural crop that provides a crucial source of edible protein and oil. Decreased amounts of saturated palmitic acid and increased amounts of unsaturated oleic acid in soybean oil are considered optimal for human cardiovascular health and therefore there has considerable interest by breeders in discovering genes affecting the relative concentrations of these fatty acids. Using a genome-wide association (GWA) approach with nearly 30,000 single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
5
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 59 publications
6
86
5
3
Order By: Relevance
“…3 decreased to half of its highest value at 7.5 kb when LD was calculated for the whole genome. Because LD in wild soybean was lower than in domesticated soybean, Leamy et al (2017) suggested that more QTLs would be found if more markers were used in wild soybean populations. This value is lower than that in wild soybean population in the studies of Zhou et al (2015) and Leamy et al (2017) (27 and >100 kb, respectively).…”
Section: Correlations Among Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 decreased to half of its highest value at 7.5 kb when LD was calculated for the whole genome. Because LD in wild soybean was lower than in domesticated soybean, Leamy et al (2017) suggested that more QTLs would be found if more markers were used in wild soybean populations. This value is lower than that in wild soybean population in the studies of Zhou et al (2015) and Leamy et al (2017) (27 and >100 kb, respectively).…”
Section: Correlations Among Traitsmentioning
confidence: 99%
“…This process increases the cost of oil and produces trans fats, which are associated with increased risk of heart disease, stroke, and diabetes (Mozaffarian and Rimm, 2006). Even so, only one recent study examined the phenotypic variation of primarily Korean and Japanese wild soybean seed compositions for protein, oil, and five fatty acids from the USDA G. soja collection (Leamy et al, 2017). Therefore, two of the goals of soybean breeding to improve oil quality are (i) to reduce the content of linolenic acid and (ii) to increase the content of oleic acid (Lee et al, 2007;Yoon et al, 2009).…”
mentioning
confidence: 99%
“…Resequencing of 28 Brazilian soybean cultivars suggested that, despite the diversification of modern Brazilian cultivars, the soybean germplasm remains very narrow because of the large number of genome regions that exhibit low diversity (Maldonado dos Santos et al, 2016). In recent years, genotyping by sequencing, skim sequencing, diversity array technology (DArT)-seq and restriction site associated DNA sequencing approaches were also employed for developing high density genetic maps, refining the QTL mapping and identifying trait linked markers in legumes Kale et al, 2015;Contreras-Soto et al, 2017;Leamy et al, 2017;Valdisser et al, 2017). Nevertheless, the percentage of missing data points and the SNP calling rates greatly reduce the number of final SNPs for different studies and this has been a concern.…”
Section: Sequencing and Genotypingmentioning
confidence: 99%
“…The QTL of chromosome 2 was also detected by Zhang et al (2004). Leamy et al (2017), in turn, found QTLs on chromosome 3 and 20 in wild soybean. Although none of these QTLs were observed in the present study, the eight QTLs identified were located in regions that have QTLs mapped for oil and fatty acid contents in the consensus map (USDA, 2016).…”
Section: Resultsmentioning
confidence: 88%
“…In Brazil, Soares et al (2008) detected QTLs on chromosomes 3, 6, 15, 18, and 19, explaining from 38.84 to 55.53% of the variation in protein content in soybean, depending on the cultivation site. QTLs for protein content in soybean have also been found on chromosome 20 (Chung et al, 2003;Nichols et al, 2006), chromosome 18 (Panthee Leamy et al, 2017), and chromosome 14 (Zhang et al, 2004;Leamy et al, 2017 None of the assessed varieties had alleles associated with high or low protein contents on all of the seven markers. The ten varieties with the highest protein content had 4-6 loci with alleles associated with high protein content on the seven markers considered.…”
Section: Resultsmentioning
confidence: 94%